The Trauma Continuum: Narrating Deprivation, Dissent and Desecration in Elnathan John and Tricia Nwaubani’s Fiction - Ajibola, Opeyemi (International Journal of Language and Literary Studies, 2023)
Northern Nigeria has in contemporary time been renowned for dissent that manifests in civil unrest, violence and insurgency. Elnathan John’s Born on a Tuesday and Tricia Nwaubani’s Buried Beneath the Baobab Tree, are closely read, to underscore the texts’ recreation of northern Nigerian young adults’ experiences of trauma occasioned by the Boko Haram insurgency. This is to foreground the writers’ insiders’ perspectives on the causes and consequences of dissent, with a view to underscoring the novels’ contribution to a nuanced understanding of dissent as a complex and multidimensional reality. Aligning with Ngugi wa Thiong’o’s certainty on the novel’s capacity to advocate for political change, and the estimation of trauma, especially within the postcolonial context as pluralistic, I read dissent, deprivation and desecration as normatively traumatogenic categories cum sites, thereby foregrounding the primacy of social contexts and historical processes in the complex interplay of place and power that undergird insurgency. The novels reveal that youths, who bear the brunt of insurgency-induced traumas the most, must arise and raise the cudgel against the inept leaders under whose watch insurgency and banditry have become the highest income-grossing enterprise, if the trauma continuum of deprivation, dissent and desecration will be terminated.